2017
DOI: 10.1155/2017/8249264
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D Supplement on Prevention of Recurrence of Preeclampsia in Pregnant Women with a History of Preeclampsia

Abstract: Introduction Preeclampsia is a pregnancy-specific syndrome. One of the hypotheses concerning the etiology of preeclampsia is vitamin D deficiency during pregnancy. Method and Materials The present study is a randomized controlled clinical trial which aims to determine the effect of vitamin D supplement on reducing the probability of recurrent preeclampsia. 72 patients were placed in control group while 70 patients were randomized to the intervention group. The intervention group received a 50000 IU pearl vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 27 publications
4
78
1
3
Order By: Relevance
“…Along with our study, several other RCTs have been published ( 11 , 86 95 ), with the main finding that a daily dose of vitamin D of 4,000 IU/safely elevated circulating 25(OH)D concentrations that, regardless of race, fully and safely normalized vitamin D metabolism and calcium homeostasis in the pregnant women. Using repeated measures, the concentration of 25(OH)D that fully normalized 1,25(OH) 2 D in our study cohort was determined on each subject and plotted to determine the point at which first order kinetics went to zero order ( 11 ), which was 100 nmol/L (40 ng/mL), the beginning point of the plateau at which the production of 1,25(OH) 2 D became substrate independent ( 11 ).…”
Section: Vitamin D Deficiency During Pregnancy: Human Studiessupporting
confidence: 72%
“…Along with our study, several other RCTs have been published ( 11 , 86 95 ), with the main finding that a daily dose of vitamin D of 4,000 IU/safely elevated circulating 25(OH)D concentrations that, regardless of race, fully and safely normalized vitamin D metabolism and calcium homeostasis in the pregnant women. Using repeated measures, the concentration of 25(OH)D that fully normalized 1,25(OH) 2 D in our study cohort was determined on each subject and plotted to determine the point at which first order kinetics went to zero order ( 11 ), which was 100 nmol/L (40 ng/mL), the beginning point of the plateau at which the production of 1,25(OH) 2 D became substrate independent ( 11 ).…”
Section: Vitamin D Deficiency During Pregnancy: Human Studiessupporting
confidence: 72%
“…26,33 Studies in HIV-uninfected women have demonstrated a variable association of lower vitamin D levels with hypertensive diseases of pregnancy, [34][35][36][37] though clinical questions around whether supplementation, and the timing and amount of supplementation, that may reduce this risk remain unanswered. 35,36,[38][39][40] The current study was novel in that it looked at the association of vitamin D levels with PIH in HIV-infected pregnant women, a group historically felt to be at increased risk for vitamin D deficiency and with variably increased risks for adverse obstetric outcomes. Our study demonstrated that lower vitamin D levels are associated with HIV disease severity in pregnant HIV-infected women with poorer disease control or on less effective treat-ment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings support previous studies mentioned above, which have proven that 4000IU/day of vitamin D supplementation is safe and effective in reducing vitamin D de ciency in pregnant women and newborns and has the most impact compared to supplementing 2000 IU/day or the recommended 400 IU/day The relationship between Vitamin D de ciency and GDM has been described frequently in literature (Zhang et al, 2008) Similar to a study conducted in neighbouring countries, our study also found an insigni cant effect of vitamin D supplementation on GDM (Asemi, Samimi, Tabassi, Shakeri, & Esmaillzadeh, 2013;Sablok et al, 2015;Tehrani, Mostajeran, & Banihashemi, 2017). The same effect of vitamin D was seen on incidence of pre-eclampsia, where although groups receiving a higher dose of vitamin D presented fewer cases of pre-eclampsia, the overall occurrence of pre-eclampsia and the difference between groups was not signi cant (Asemi et al, 2013;Naghshineh & Sheikhaliyan, 2016;Sablok et al, 2015;Sasan, Zandvakili, Sou zadeh, & Baybordi, 2017).…”
Section: Discussionmentioning
confidence: 88%